A Locational Study of R. Murray Schafer’s Music for Wilderness Lake [1979] - Teetsel, Sarah (CAML Review / Revue de l’ACBM, 2025)
Music for Wilderness Lake [1979] was a pioneering composition in the development of Canadian composer R. Murray Schafer’s (1933–2021) environmental works. Envisioned as a performance for twelve trombones gathered around Southern Ontario’s O’Grady Lake, it continuously evolved as the realities of the outdoor location shaped the compositional process and the premiere performance. Schafer was prompted to think about how an outdoor, rural location affects musical performances and what concessions it required. Despite the significant role Music for Wilderness Lake played in Schafer’s compositional output, it is too often scripted as a first step to his later environmental works. In this article, the author recontextualizes Music for Wilderness Lake by exploring the experimentation that took place as Schafer’s vision was adapted to performance and logistical challenges. One of the unique features of Music for Wilderness Lake is the use of a central raft on a lake, from which Schafer cued the full ensemble during the premiere. By examining the performance site, this article highlights how some of the aspects of the location that Schafer found exciting—wide spatialization of performing forces and lively echoes—affected the development of Music for Wilderness Lake. Using contemporaneous articles (Littler 1979, MacMillan 1979, and Sweete 1980); interviews (including Westerkamp 1981); sketches of the location; and the film made of the performance (Music for Wilderness Lake, 1980, Fichman-Sweete Productions); this article explores why O’Grady Lake was chosen for the premiere and how the space helped develop specific relationships among participants based on spatialization and instrumental groupings.